Bilgi Edinme Hakkı Kanunu ve Kurumsal Bilgi Yönetimi İlişkisi / Freedom of Information Law and Relation with Organizational Knowledge Management - Hakan Anameriç (Bilgi Dünyası, 2004)
E-Government process in Turkey as one of the adoption projects encompasses many legislation including some regulations. One of these regulation is that Freedom of Information Act that will provide to manage their information and enable citizens acquire information efficiently and prodocutively. Laws that are made for this purpose in 50 countries and effective as of democratic and flexible public management. By means of that, the regulations work in the aim of public’s fair use and access to information in terms of essences and rules in the basis of equality, objectivity and openness principles. Therefore, information that are produced by the foundation and institutions can be under control and described to extent of its security and sharability and information.